Integration of GeoGebra in Problem-Based Learning to Improve Students' Problem-Solving Skills - Suratno, Joko; Waliyanti, Ida Kurnia (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Learning mathematics requires the development of problem-solving abilities. However, problem-solving requires additional focus, particularly in the context of schools. Therefore, alternatives are needed to teach students how to solve problems through GeoGebra in problem-based learning. The goal of this study was to thoroughly and in-depth investigate how the use of GeoGebra in problem-based learning affects students' capacity for problem-solving. Quasi-experimental research methodology is employed. The Posttest-Only Design with Nonequivalent Groups was the quasi-experimental design in this work. According to the data analysis, incorporating GeoGebra into problem-based learning significantly impacts students' ability to solve problems.